Neighborhood Geometric Structure Preserving Variational Auto-Encoder for Smooth and Bounded Data Sources - Chen, Xingyu; Wang, Chunyu; Lan, Xuguang; Zheng, Nanning; Zeng, Wenjun (IEEE Transactions on Neural Networks and Learning Systems (to appear), 2021)
.